Circular Economy: Municipal Solid Waste and Landfilling Analyses in Slovakia - Emese Tokarčíková; Mária Ďurišová; Terézia Trojáková (Economies)
The pursuit of shifting Slovakia towards a circular economy is met with a multitude of obstacles, including the pervasive consumerist mindset among Slovakians. This mindset favors packaged food, leading to its improper disposal in municipal waste instead of being recycled. Furthermore, the inclination towards landfills poses a significant challenge in the management of municipal solid waste (MSW). To address this issue, a quantitative analysis was conducted using developed and validated models, incorporating various factors related to MSW management in Slovakia. Our study confirmed the significance of parameters such as MSW management costs and population size in the amount of MSW generated. Furthermore, our findings include a short-term forecast for MSW generation in Slovakia for the next two years. These results, based on quantitative data, provide valuable insights for policymakers and waste management authorities in Slovakia, emphasizing the urgent need for a transition towards a more sustainable and circular economy.